Kikuchi Fujimoto as an Initial Presentation of Systemic Lupus Erythromatosis - Basnet, Srijana; Shrestha, Laxman; Shrestha, Prabina (Journal of Nepal Paediatric Society, 2021)
Kikuchi-Fujimoto Disease (KFD) is a rare benign, condition of necrotising histiocytic lymphadenitis. In this case report, we discuss a case of 10 year old male patient who presented with a fever, rash and generalised lymphadenopathy that was not attributable to the more common causes. Axillary lymph node biopsy confirmed the diagnosis of KFD. Treatment with prednisolone improved his symptoms but after six months he had recurrence of his symptoms. He was investigated again and finally met diagnostic criteria for SLE. This case report highlights importance of close follow up in a child with KFD.